Functional reconstruction of complex tendo Achilles defect by free latissimus dorsi muscle flap - Vaibhav Khanna; Romesh Kohli; Satendar Tulsi; Sandeep Garg; Divya Upadhyaya (Indian Journal of Plastic Surgery, 2012)
Managing the complex tendo Achilles defect involves reconstructing the Achilles tendon as well as providing soft tissue cover to the heel area. The advent of microsurgery has revolutionised the reconstruction of this difficult defect providing a number of options to the reconstructive surgeon. We present a case of complex tendo Achilles defect reconstructed by the latissimus dorsi free flap.